Evaluation of the impact of the COVID-19 lockdown on BMI in children and adolescents with or without obesity - Albane B. R. Maggio; Claudine Gal-Dudding; Xavier Martin; Catherine Chamay-Weber (BMC, 2022)
Abstract Background In Switzerland, from March 15th to May 11th 2020, schools and most shops were closed nationwide due to the COVID-19-related lockdown. This cessation of activities may have impacted weight gain in children and adolescents. The aims of our study were to evaluate the effects of the COVID-19 lockdown on the BMI of children and adolescents in treatment for obesity, and to compare its evolution to that of the previous year at the same time, as well as to that of normal-weight children. Methods This retrospective study gathered demographic and anthropometric data from subjects aged 6-18 years both with normal weight and with obesity, who attended our hospital clinics at four time points: before and after the lockdown period in 2020, and at the same times of the year in 2019. We used paired t-tests to assess weight, BMI and BMI z-score changes, linear and standard multiple regressions, independent Student's t-tests or Chi-square tests to compare groups, and Pearson correlation coefficient when appropriate. Results Forty-seven children with obesity and 18 normal-weight subjects had complete data for the 4 visits. The mean BMI increased in both groups during the lockdown (obese: + 0.96 ± 1.5 vs. control: + 0.51 ± 0.1), however the increase was significantly more important in the subjects with obesity compared to the same period in 2019 (2019: + 0.33 ± 1.0; mean difference between 2019 and 2020: + 0.63 ± 2.0 p = 0.034). Conclusion The COVID-19 lockdown had a negative impact on the BMI of youth with obesity. Interestingly we observed extreme changes in this population, which was not the case in normal-weight children. Therefore, families with a child with obesity must be actively supported during these stressful and obesogenic periods of confinement.